A preprocedural risk score predicts acute kidney injury following primary percutaneous coronary intervention. Issue 2 (14th August 2020) - Buratti, Stefano; Crimi, Gabriele; Somaschini, Alberto; Cornara, Stefano; Camporotondo, Rita; Cosentino, Nicola; Moltrasio, Marco; Rubino, Mara; De Metrio, Monica; Marana, Ivana; De Servi, Stefano; Marenzi, Giancarlo; et al.
Abstract: Background: Reliable preprocedural risk scores for the prediction of Contrast‐Induced Acute Kidney Injury (CI‐AKI) following Percutaneous Coronary Intervention (pPCI) in patients with ST‐elevation myocardial infarction (STEMI) are lacking. Aim of this study was to derive and validate a preprocedural Risk Score in this setting. Methods: Two prospectively enrolled patient cohorts were used for derivation and validation ( n = 3, 736). CI‐AKI was defined as creatinine increase ≥0.5 mg/dl <72 h postpPCI. Odds ratios from multivariable logistic regression model were converted to an integer, whose sum represented the Risk Score. Results: Independent CI‐AKI predictors were: diabetes, Killip class II‐III (2 points each), age > 75 years, anterior MI (3 points), Killip class IV (4 points), estimated GFR < 60 ml/min/1.73m 2 (5 points). The Risk Score c‐statistic was 0.84 in both cohorts. Compared with patients with Risk Score ≤ 4, the relative risks of CI‐AKI among patients scoring 5–9 were 6.2 (derivation cohort) and 7.1 (validation cohort); among patients scoring ≥10, 19.8, and 21.4, respectively. Conclusions: Among STEMI patients, a simple preprocedural Risk Score accurately and reproducibly predicted the risk of CI‐AKI, identifying ¼ of patients with a seven‐fold risk and 1/10 of patients with a 20‐fold risk. This knowledge may help tailored strategies, including delaying revascularization of nonculprit vessels in patients at high risk of CI‐AKI.